Hak Politik Kelompok Minoritas : Studi Kasus pada Kelompok Masyarakat Protestan dalam Pemilihan Umum Tahun 2019 di Kecamatan Cihideung Kota Tasikmalaya - Ilham Ramadhani; Fitriyani Yuliawati; Randi Muchariman (Epistemik Press, 2023)
This article aims to determine the political rights that occur in Protestant minority gropus during during the 2019 general election taking place In Cihideung District, Tasikmalaya City, with the majority of the population being Muslim, so it is very interesting to discuss the political rights of other religious minorities, one of which is Protestants. Political rights theory taken from legal products, such as the 1945 Constitution of the Republic of Indonesia, Law Number 39 of 1999 concerning Human Rights, the text of the Universal Declaration of Human Rights, and the text of the International Covenant on Civil and Political Rights as a basis for sharpening theory and strengthening of the political rights of Protestant groups. This study also uses qualitative research methods with a case study research approach. The informant collection technique used purposive sampling, as well as data collection techniques in this study using interview techniques and documentation studies. Then, in terms of data validity, this research uses data source triangulation techniques. The results of this study are the realization of political rights in Protestant community groups during the 2019 elections, in reality there were dynamics during their implementation. The lack of implementation of political rights can also affect human rights and democracy in the Protestant community in Cihideung District, Tasikmalaya City. Then, the process of Minority Politics towards the Protestant community which is still lacking in its implementation also means that the political rights of the Protestant community are still not optimal.